Psychological aftermaths of Covid-19: a study of diagnosed and never diagnosed adults - Sadiq, Riffat (Journal of the Pakistan Medical Association, 2023)
A cross-sectional comparative study was conducted from March 2021 to May 2022 in Faisalabad district, Pakistan, to rule out the prevalence and comparison of psychological aftermaths of Covid-19 pandemic for adults with and without a diagnosis for the disease. For data collection, a sample of 218 individuals was recruited through purposive sampling technique. Participants, with and without the diagnosis of Covid-19, experienced significant depression, anxiety, stress, and somatic symptoms amid the pandemic. Further analysis revealed that adults diagnosed with Covid-19 significantly reported more depression (t= 2.76, df = 216, p = .006, Cohen’s d=0.37), more stress (t= 3.08, df = 216, p = .002, Cohen’s d= 0.41), and more somatic symptoms (t= 10.83, df = 216, p =.000, Cohen’s d= 1.46) as compared to adults who were not diagnosed with the disease. —Continue